COOPERATION OF ACTORS IN MAINTENANCE OF URBAN GREEN SYSTEMS IN DAR ES SALAAM CITY: The case of Mbweni, Kijichi and Buyuni - Helene Stephene Francis; Makarius Victor Mdemu; Ally Hassan Namangaya (African Journal on Land Policy and Geospatial Sciences, 2022)
Green systems play a significant role in the resilience of cities. However, the rate of disappearance is increasing in the global south and affects the resilience of cities. But their disappearance has been associated with inadequate cooperation of actors.